An open-data open-model framework for hydrological models' integration, evaluation and application. (April 2020) - Salas, Daniel; Liang, Xu; Navarro, Miguel; Liang, Yao; Luna, Daniel
Abstract: To tackle fundamental scientific questions regarding health, resilience and sustainability of water resources which encompass multiple disciplines, researchers need to be able to easily access diverse data sources and to also effectively incorporate these data into heterogeneous models. To address these cyberinfrastructure challenges, a new sustainable and easy-to-use Open Data and Open Modeling framework called Meta-Scientific-Modeling (MSM) is developed. MSM addresses the challenges of accessing heterogeneous data sources via the Open Data architecture which facilitates integration of various external data sources. Data Agents are used to handle remote data access protocols, metadata standards, and source-specific implementations. The Open Modeling architecture allows different models to be easily integrated into MSM via Model Agents, enabling direct heterogeneous model coupling. MSM adopts a graphical scientific workflow system (VisTrails) and does not require re-compiling or adding interface codes for any diverse model integration. A study case is presented to illustrate the merit of MSM. Graphical abstract: Image 1 Highlights: A novel open data open model framework based on scientific workflow. Automated machine-to-machine access from external data sources to models. Easy model sharing and heterogeneous/diverse model couplings. No central administration required for the framework system and shared models. System-wide sophisticated data fusion scheme for data and/or model outputs.